Low gas emission and gas adsorption sealant film
Patent Information
- Application Number
- JP2020165503
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-30
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2040-09-30
AI Technical Summary
【0006】 本発明により、シーラントフィルムそれ自体から発生するガス及びシーラントフィルムが接する空間からのガスを吸着し、ガス放出量が少なく、経時劣化による包装体内外へのガスの出入り及び放出を抑制する、シーラントフィルム、及び該シーラントフィルムを用いて作製された積層体、包装材料、包装体を得ることができる。
Smart Images

Figure 0007635527000009 
Figure 0007635527000010 
Figure 0007635527000011
Abstract
Description
[Technical field]
[0001] The present invention relates to a gas-adsorbing sealant film with low outgassing property that adsorbs gas generated from the sealant film itself and gas from a space with which the sealant film is in contact, and thus emits only a small amount of gas. [Background technology]
[0002] 2. Description of the Related Art In recent years, some packages require airtightness, such as vacuum packaging, in order to prevent contamination or deterioration of the package contents or to prevent leakage of the package contents. Depending on the type of contents, the purpose may be to make the pressure inside the package higher than atmospheric pressure to prevent gas from entering the package from the outside, or to make the pressure inside the package lower than atmospheric pressure to prevent gas from leaking from inside the package to the outside, or simply to maintain a pressure inside the package lower or higher than atmospheric pressure. If the packaging material has a high effect of imparting airtightness, the packaging container that directly contains the contents can be simplified, making it possible to reduce the weight and space of the package. However, conventional packaging materials are prone to gas permeation when damaged or deteriorated over time, resulting in a rapid loss of airtightness. For example, one reason for gas intrusion into the inside of a package due to deterioration over time caused by the packaging material is the intrusion of air as it permeates the outer packaging material. In order to improve the gas barrier properties of the packaging material, laminated films having a metal aluminum foil with a thickness of about 7 to 15 μm as a gas barrier layer have been mainly used for the packaging material, and laminated films having an additional layer made of a vapor-deposited film or coated film of various inorganic materials have been proposed (Patent Document 1). However, these have been insufficient in terms of maintaining stable gas barrier properties over the long term. A method has been proposed in which a porous material such as synthetic zeolite is incorporated into the sealant layer of the packaging material to adsorb gas components and thereby maintain the degree of vacuum inside the package (Patent Document 2). However, this method is insufficient in terms of maintaining a stable insulation effect over the long term, due to the limited types of gases that can be adsorbed, the low heat resistance of the resin that constitutes the sealant layer, and the large amount of outgassing. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2008-087176 A [Patent Document 2] JP 2018-189220 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention aims to provide a sealant film that adsorbs gas generated from the sealant film itself and gas from the space with which the sealant film is in contact, and that emits only a small amount of gas, thereby suppressing the entry / exit and emission of gas into and out of the package due to deterioration over time, as well as a laminate, packaging material, and packaging body made using the sealant film. [Means for solving the problem]
[0005] As a result of various investigations, the present inventors have found that the above object can be achieved by a sealant film that at least emits a small amount of gas and has gas adsorption properties. That is, the present invention is characterized in the following points. 1. A low gas-emission gas-adsorbing sealant film that adsorbs gas generated from the sealant film itself and gas from the space that the sealant film contacts, The gas may be a hydrocarbon, an aldehyde, a ketone, a carboxylic acid, an ester, an alcohol, or the like. and carbon dioxide; The low gas emission gas adsorption sealant film contains a low gas emission resin having heat sealability and a gas adsorbent, The low gas emission resin has a density of 0.915 g / cm 3 More than 0.935g / cm 3 Characterized in that The low outgassing gas adsorbing sealant film. 2. The content of the low gas-releasing resin in the entire low gas-releasing gas adsorbing sealant film is 70% by mass or more and 99.9% by mass or less; The gas adsorbent content in the layer containing the gas adsorbent is 0.1% by mass or more and 30% by mass or less. 2. The low outgassing gas adsorbing sealant film according to 1 above. 3. A gas adsorbing sealant film with low outgassing properties as described in 1 or 2 above, characterized in that the low outgassing resin is a polyethylene-based resin. 4. A low outgassing gas adsorption sealant film described in any one of 1 to 3 above, characterized in that the concentration of soluble total organic carbon (TOC) contained in the film made of the low outgassing resin is 1.5 ppm or more and 250 ppm or less. 5. The low outgassing gas adsorption sealant film has a carbon number of 16 organic gas component released when heated in air at 90°C for 60 minutes, and the amount of the low outgassing gas adsorption sealant film per unit volume of the low outgassing gas adsorption sealant film is 10 μg / cm 3 More than 1000μg / cm 3 5. The gas adsorbing sealant film with low gas release according to any one of the above items 1 to 4, characterized in that: 6. A low outgassing gas adsorbing sealant film described in any one of 1 to 5 above, characterized in that the low outgassing resin is one or a combination of two or more selected from the group consisting of medium density polyethylene, low density polyethylene and linear low density polyethylene. 7. A low gas release gas adsorbent sealant film according to any one of 1 to 6 above, characterized in that the gas adsorbent comprises one or a combination of two or more selected from the group consisting of hydrophobic zeolite, molecular sieve, metal-organic framework (MOF), and activated carbon. 8. The low outgassing gas adsorption sealant film has a gas adsorption layer and a heat seal layer, the gas adsorption layer is a layer containing the low gas release resin and the gas adsorbent, the heat seal layer contains the low gas release resin and has heat sealability; At least one outermost layer of the low outgassing gas adsorbent sealant film is a heat seal layer, The low gas-releasing resin contained in the gas adsorption layer and the low gas-releasing resin contained in the heat seal layer are the same or different. 8. A gas adsorbing sealant film with low gas release properties as described in any one of 1 to 7 above. 9. The gas adsorbing sealant film with low outgassing properties as described in any one of 1 to 8 above, further comprising an antioxidant. 10. The low outgassing, gas-adsorbing sealant film according to claim 9, characterized in that the content of the antioxidant is 0.005 mass % or more and 0.5 mass % or less in the total low outgassing, gas-adsorbing sealant film. 11. The antioxidant is contained in the gas adsorption layer and / or the heat seal layer, The antioxidant contained in the gas adsorption layer and the antioxidant contained in the heat seal layer are the same or different. 11. A low gas-releasing, gas-adsorbing sealant film according to 9 or 10 above. 12. A gas adsorbing laminate with low outgassing properties, produced using the gas adsorbing sealant film with low outgassing properties described in any one of 1 to 11 above. 13. A gas-adsorbing packaging material with low outgassing properties, produced using the gas-adsorbing laminate described in 12 above. 14. A gas-adsorbing packaging body with low gas emission, produced using the gas-adsorbing packaging material described in 13 above. Effect of the Invention
[0006] According to the present invention, it is possible to obtain a sealant film that adsorbs gas generated from the sealant film itself and gas from the space with which the sealant film is in contact, and that emits a small amount of gas and suppresses the entry / exit and emission of gas into and out of the package due to deterioration over time, as well as a laminate, packaging material, and package made using the sealant film. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of the layer structure of a low outgassing gas adsorbent sealant film of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an example of another embodiment of the layer structure of the low outgassing gas adsorbent sealant film of the present invention. [Diagram 3] FIG. 2 is a schematic cross-sectional view showing another example of the layer structure of the low outgassing gas adsorbent sealant film of the present invention. [Figure 4] 1 is a schematic cross-sectional view showing an example of the layer structure of a low outgassing gas adsorbing laminate or a low outgassing gas adsorbing packaging material of the present invention. [Diagram 5] FIG. 1 is a schematic cross-sectional view showing an example of the configuration of a low gas release gas adsorption packaging body of the present invention.
[0008] In each drawing, the size and ratio of the components may be changed or exaggerated for ease of understanding. Also, for ease of understanding, parts that are not necessary for the explanation or repeated reference numerals may be omitted. Although not shown in the drawings, an adhesive layer may be provided between each layer. Furthermore, if necessary, in order to strengthen the adhesive strength (adhesion strength) between each layer, the laminated surfaces of each layer may be subjected in advance to a physical surface treatment such as corona discharge treatment, ozone treatment, plasma treatment, glow discharge treatment, sandblasting treatment, etc., or a chemical surface treatment such as an oxidation treatment using chemicals. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The low outgassing gas adsorbent sealant film, the low outgassing gas adsorbent laminate, the low outgassing gas adsorbent packaging material, and the low outgassing gas adsorbent packaging body of the present invention will be described in more detail below. Specific examples will be shown, but the present invention is not limited thereto. In the present invention, the terms film and sheet are used synonymously.
[0010] <Low gas emission gas adsorption sealant film> The low outgassing, gas adsorbing sealant film of the present invention contains a low outgassing resin having heat sealability and a gas adsorbent, and has heat sealability, low outgassing properties, and is capable of adsorbing gas. Due to the above characteristics, the gas adsorbent sealant film with low gas emission of the present invention is suitable as a sealant film for vacuum packaging. The low outgassing gas adsorbent sealant film may have a single layer structure or a multi-layer structure of two or more layers. For example, it may be composed of a gas adsorption layer containing a low gas-releasing resin and a gas adsorbent, and a heat seal layer containing a low gas-releasing resin, or it may have a three-layer structure in which a gas adsorption layer is sandwiched between two heat seal layers.
[0011] The content of the low gas-releasing resin in the entire low gas-releasing gas adsorption sealant film is preferably 70% by mass or more and 99.9% by mass or less, more preferably 80% by mass or more and 99.9% by mass or less, and even more preferably 90% by mass or more and 99.9% by mass or less. If it is less than the above range, the low gas-releasing property of the low gas-releasing gas adsorption sealant may be insufficient, and if it is more than the above range, it is difficult to balance various physical properties and workability, but the low gas-releasing property is not improved much.
[0012] The content of the gas adsorbent in the layer containing the gas adsorbent is preferably 0.1% by mass or more and 30% by mass or less, and more preferably 0.5% by mass or more and 25% by mass or less. If the content is less than the above range, the gas adsorption effect may be insufficient, and if the content is more than the above range, the film formability may be deteriorated. Here, the layer containing a gas adsorbent refers to the entire low outgassing, gas adsorbing sealant film when the low outgassing, gas adsorbing sealant film is composed of only one layer, and refers to, for example, the gas adsorbing layer when the low outgassing, gas adsorbing sealant film is a multi-layer structure having a gas adsorption layer and a heat seal layer, etc.
[0013] When the low outgassing gas-adsorbing sealant film has a multi-layer structure having a gas adsorption layer, a heat seal layer, etc., in order to improve the heat sealability and lamination properties, it is preferable that the outermost layer on at least one side of the low outgassing gas-adsorbing sealant film is a heat seal layer, and it is more preferable that the outermost layers on both sides are heat seal layers. Furthermore, the low gas-releasing resin contained in the gas adsorption layer and the low gas-releasing resin contained in the heat seal layer may be the same or different.
[0014] The gas adsorption and low outgassing properties of the low outgassing gas adsorbent sealant film can be adjusted by adjusting the film thickness. The thickness of the low gas release gas adsorption sealant film is preferably 25 μm or more and 150 μm or less, more preferably 30 μm or more and 100 μm or less, in order to have a good balance between heat sealability, gas adsorption, and low gas release. If it is thinner than the above range, the heat sealability and / or gas adsorption may be insufficient, and if it is thicker than the above range, the low gas release may be inferior.
[0015] And, the low outgassing, gas adsorbing sealant film may further contain minor amounts of slip agents, antiblocking agents, antioxidants, solvents, and other additives. The low gas release gas adsorbent sealant film of the present invention preferably contains an antioxidant in order to suppress the generation of gas released due to resin deterioration in a high temperature environment. Conversely, it is preferable to limit the use of additives that may increase the amount of gas released at high temperatures.
[0016] (Gas to be adsorbed) The gas components to be adsorbed in the present invention are mainly gas components originally contained in the low outgassing gas adsorbent sealant film of the present invention, gas components consisting of resin decomposition products generated by decomposition of the resin in the low outgassing gas adsorbent sealant film by heating such as heat sealing or irradiation with UV or EB, etc., and gas components present in the atmosphere. Here, examples of gas components originally contained in the low outgassing, gas-adsorbing sealant film include gas components contained in the raw materials constituting the low outgassing, gas-adsorbing sealant film, and gas components generated due to the thermal history, etc., when forming the low outgassing, gas-adsorbing sealant film.
[0017] Specific examples of gases to be adsorbed include organic substances with relatively small molecular weights and carbon dioxide. The organic matter is a gas component derived from the low gas-releasing gas-adsorbing sealant film, Many of the compounds that are carbon atoms of the carbon component have 1 to 16, and the most common type is hydrocarbons, with other examples being aldehydes, ketones, carboxylic acids, alcohols, and esters.
[0018] Specific examples of hydrocarbons include propane, propene, butane, isobutane, 2-methylbutane, butene, isobutene, 2-methylpentane, 3-ethylpentane, 2,2-dimethylpentane, 3,3-dimethylpentane, hexane, cyclohexane, 2-methylhexane, 3-methylhexane, 2,5-dimethylhexane, heptane, 2-methylheptane, 3-methylheptane, 3-ethylheptane, 2,2,4,6,6-pentamethylheptane, 3-ethyl-3-methylheptane, 3-methylheptene, octane, 2-methyloctane, 4-ethyloctane, nonane, 3-methylnonane, decane, and dodecane.
[0019] Specific examples of aldehydes include formaldehyde, acetaldehyde, 2-methylpropanal, and 3-methylbutanal.
[0020] Specific examples of ketones include acetone, MEK, MIBK, and 3,3-dimethyl-2-butanone.
[0021] Specific examples of carboxylic acids include acetic acid, isovaleric acid, 2-methylpropanoic acid, and 2,2-dimethylpropanoic acid.
[0022] Specific examples of esters include ethyl acetate and butyl acetate.
[0023] Specific examples of alcohols include 2-methyl-2-propanol, 2-methylpropanol, ethanol, and 1-propanol.
[0024] Carbon dioxide originates from atmospheric components, aldehydes, ketones, and carboxylic acids originate from the thermal history of the gas adsorbing sealant film and atmospheric components, and esters originate from the gas adsorbing sealant film or the adhesive layer of the low outgassing gas adsorbing laminate.
[0025] [Gas adsorption layer] The gas adsorption layer is a layer containing a gas adsorbent and having high gas adsorption properties, and preferably further contains a low gas release resin as a binder resin in order to maintain low gas release properties. However, other resins and various additives such as antioxidants can be contained within a range that does not significantly impair the gas adsorption properties and low gas release properties. The gas adsorbing layer in the low outgassing gas adsorbing sealant film may be one layer or two or more layers having the same or different compositions.
[0026] In order to exhibit good gas adsorption properties, the thickness of the gas adsorption layer is preferably 5 μm or more and 80 μm or less, more preferably 7 μm or more and 75 μm or less. If the thickness is thinner than the above range, the gas adsorption properties may be insufficient, and if the thickness is thicker than the above range, the gas adsorption properties may not be improved significantly, and the rigidity of the low gas release gas adsorption sealant film may become too strong, resulting in a decrease in workability.
[0027] [Heat seal layer] The heat seal layer is a layer containing a low gas releasing resin and has high heat sealability. In order to have high heat sealability, it is preferable that the heat seal layer does not contain a gas adsorbent. In order to achieve both high heat sealability and low gas release, the heat sealable resin contained is preferably a low gas release resin. However, various additives such as gas adsorbents, other resins, and antioxidants may be contained within the range that does not significantly impair the heat sealability and low gas release properties. The low outgassing gas adsorbing sealant film may contain one heat seal layer or two or more layers having the same or different compositions.
[0028] In order to exhibit good heat sealability, the thickness of the heat seal layer is preferably 3 μm or more and 30 μm or less, more preferably 5 μm or more and 20 μm or less. If the thickness is thinner than the above range, the heat sealability may be insufficient, and if the thickness is thicker than the above range, the heat sealability may not be improved much, and the rigidity of the low gas release gas adsorption sealant film may become too weak, resulting in a decrease in workability.
[0029] [Low gas emission resin] A low gas release resin is a resin that releases a small amount of gas, and the amount of gas released varies depending on the shape and thermal history of the resin. By incorporating a low outgassing resin having heat sealability into a low outgassing, gas-adsorbing sealant film, the low outgassing, gas-adsorbing sealant film can be imparted with heat sealability, thereby reducing the amount of gas released and suppressing the passage or release of gas.
[0030] The amount of gas released from low gas release resins is highly correlated with the concentration of elutable total organic carbon (TOC) contained in the low gas release resins. TOC is the concentration of the total amount of organic matter (organic carbon bodies) that can be oxidized in water, expressed as a carbon concentration, and is used as one of the most representative water quality indicators, and is standardized in JIS K0805 (Total Organic Carbon (TOC) Automatic Meter) and other standards.
[0031] The concentration of soluble total organic carbon (TOC) contained in the film made of the low gas-releasing resin in the present invention is preferably 1.5 ppm or more and 250 ppm or less, and more preferably 5 ppm or more and 200 ppm or less. It is difficult to prepare a film having a concentration lower than the above range, and it is difficult to show a significant difference in practical effect. If it is higher than the above range, the gas-releasing property of the low gas-releasing resin may be insufficient.
[0032] The reason why the concentration of elutable TOC for the low outgassing resin as a single raw material is measured in a film state rather than in the state of raw material pellets, etc., is that when the low outgassing resin is made into a film to form a low outgassing gas adsorption sealant layer, etc., it is subjected to various heat histories, etc., which may increase the amount of eluted TOC.
[0033] The concentration of soluble total organic carbon (TOC) contained in the film made of the above-mentioned low outgassing resin is determined, for example, by filling a pouch made of a film made of the low outgassing resin of the present invention with distilled water as the filling water, allowing the organic carbon to elute, measuring the TOC concentration of the filling water, subtracting the TOC concentration of the filling water before filling as a blank to calculate the increase in TOC concentration, and then calculating the soluble TOC concentration contained in the film made of the low outgassing resin.
[0034] The increase in TOC concentration of the filling water is preferably 0.01 ppm or more and 1.5 ppm or less, more preferably 0.02 ppm or more and 1.45 ppm or less, and even more preferably 0.025 ppm or more and 1.4 ppm or less. It is difficult to prepare something less than the above range, and it is difficult to show a significant difference in practical effect. If it is more than the above range, the low gas release resin may have insufficient low gas release properties. From the viewpoint of both cost and performance, it is preferable that it is in the above range.
[0035] More specific conditions, depending on the application, are to keep the temperature of the water to 40℃~80℃. It is preferable to set the temperature during storage at 25°C to 50°C for a storage period of several days to 4 weeks, and to measure the TOC concentration of the filled water with a total organic carbon meter or HS-GC.
[0036] In the present invention, the elutable TOC concentration contained in the resin film made of low outgassing resin is preferably calculated by filling a pouch made of a resin film made of low outgassing resin and having an inner dimension of 15 cm x 44 cm with 1000 g of distilled water (distilled water for high performance liquid chromatography, manufactured by Junsei Chemical Co., Ltd.) at 65°C as the filling water, sealing it, storing it at 35°C for 2 weeks, and then measuring the TOC concentration of the filled water with a TOC-L total organic carbon meter (manufactured by Shimadzu Corporation) as the standard method.
[0037] For example, when a pouch measuring 15 cm x 44 cm x 50 μm in thickness is used and 1,000 g of water is filled, the concentration C of leachable TOC contained in the film made of low gas releasing resin is calculated from the increase in TOC concentration in the filled water as shown below. Filled water (distilled water) weight: W1 = 1000 [g] Density of film made of low gas emission resin: S [g / cm 3 ] Pouch size: 15cm x 44cm x 50μm thick Pouch weight: W2=15×44×50×10 -4 ×2×S=6.6×S[g] Concentration of soluble TOC contained in a film made of low gas emission resin: C [ppm] Increase in TOC concentration in filling water: X [ppm] Then, Total weight of extractable TOC contained in the film made of low gas emission resin = C × W2 [g] This dissolves in W1[g] of water, so X=C×W2 / W1=C×6.6×S×10 -3 [ppm] The TOC concentration C of the elutable TOC contained in the film made of low gas release resin is calculated from the following formula: C = X / (6.6 × S × 10 -3 ) [ppm] For example, the density S of the film made of low gas releasing resin that constitutes the pouch is 0.92 [g / cm 3 ], if the increase in TOC concentration of the filling water is 0.01 [ppm], C = 0.01 / (6.6×0.92×10 -3 )=1.64[ppm] It is calculated as follows:
[0038] The density of the low gas emission resin is 0.915g / cm 3 More than 0.935g / cm 3 Less than 0.919 g / cm is preferred. 3 More than 0.933g / cm 3If the density is within the above range, the amount of gas released from the organic material tends to be low.
[0039] The MFR (melt flow rate) of the low gas release resin is preferably 0.2 g / 10 min or more and 10 g / 10 min or less, and more preferably 0.5 g / 10 min or more and 7 g / 10 min or less. If the MFR is within the above range, even if it is mixed with other resins or gas adsorbents, it can maintain a good MFR and exhibit good film-forming properties and adhesive properties.
[0040] As the low gas-releasing resin, a polyethylene resin (low gas-releasing polyethylene resin) is preferable because it has excellent heat sealability, resistance to UV or EB irradiation and heating, and resistance to decomposition. Low gas release polyethylene resins originally contain a small amount of gas that can be released, and are resistant to UV or EB irradiation and heating and therefore difficult to decompose, thereby enabling the amount of gas released to be reduced.
[0041] Specific examples of polyethylene types of low gas emission polyethylene resins include low density polyethylene. Examples of the low outgassing polyethylene include, but are not limited to, low density polyethylene (LDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), linear low density polyethylene (LLDPE), ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, ethylene-methyl methacrylic acid copolymer, ethylene-propylene copolymer, and mixtures of these resins.
[0042] Among the above, one or a combination of two or more selected from the group consisting of MDPE, LDPE and LLDPE is preferred. The LLDPE is preferably one or a combination of two or more selected from the group consisting of C4-LLDPE, C6-LLDPE, and C8-LLDPE, and C6-LLDPE is more preferable.
[0043] Here, C4-LLDPE is a linear low-density polyethylene made of a copolymer of ethylene and 1-butene, C6-LLDPE is a linear low-density polyethylene made of a copolymer of ethylene and 1-hexene and / or 4-methyl-1-pentene, and C8-LLDPE is a linear low-density polyethylene made of a copolymer of ethylene and 1-octene. Each of the molecular structures has an ethylene-derived LLDPE main chain with side chains having 4, 6 and 8 carbon atoms derived from 1-butene, 1-hexene and / or 4-methyl-1-pentene and 1-octene, respectively.
[0044] In order to keep the amount of released gas contained in the resin low, for example, it is effective to reduce the amount of unreacted raw materials, low molecular weight products, and by-products, and to remove the polymerization catalyst when producing the resin.Specific examples of such methods include improving the purity of raw materials, precisely controlling conditions such as reaction temperature and pressure, removing unreacted raw materials, low molecular weight products, by-products, and polymerization catalysts by distillation or washing, and preventing oxidation due to exposure to oxygen in the air at high temperatures. Another method is to limit the use of additives that may increase the amount of outgassing when the resin is pelletized or filmed, and to prevent oxidation due to high temperatures. Specific additives include lubricants, antioxidants, antiblocking agents, solvents, etc.
[0045] [Gas adsorbent] In the present invention, the gas adsorbent preferably contains one or a combination of two or more selected from the group consisting of hydrophobic zeolite, molecular sieve, metal-organic framework (MOF), and activated carbon.
[0046] (Hydrophobic Zeolite) In the present invention, the hydrophobic zeolite used as the gas adsorbent preferably has a SiO2 / Al2O3 molar ratio of 2 / 1 to 10000 / 1, more preferably 30 / 1 to 3000 / 1. When the molar ratio is within the above range, the hydrophobicity and pore size are well balanced, and good gas adsorption properties can be achieved. Hydrophobic zeolite is preferably used because it maintains its gas component adsorption effect even when exposed to temperatures of 230° C. or higher. The hydrophobic zeolite may have any external shape, such as a sphere, a rod, an ellipse, or the like, and may be in any form, such as a powder, a lump, or a granule. From the viewpoints of uniform dispersibility, kneading characteristics, film-forming properties, and the like, when dispersed in a resin, the powder form is preferred.
[0047] In the present invention, the average particle size of the hydrophobic zeolite may be any average particle size depending on the application. The average particle size is preferably 0.01 μm or more and 30 μm or less, and more preferably 0.1 μm or more and 20 μm or less. Here, the average particle size is a value measured by a dynamic light scattering method. If the average particle size is smaller than the above range, the hydrophobic zeolite is likely to aggregate and the dispersibility tends to decrease.If the average particle size is larger than the above range, the film-forming property of the layer containing the hydrophobic zeolite tends to be poor, so it tends to be difficult to add a large amount of hydrophobic zeolite, and the surface area is also reduced, so there is a possibility that a sufficient gas adsorption effect cannot be obtained.
[0048] Hydrophobic zeolites are hydrophobic, so they are difficult to adsorb highly polar water molecules, but conversely have a high affinity with organic gases with low polarity, and also have a high affinity with other gas components with low polarity, hydrophobic gases, and lipophilic gases (including solvent-based gases), and are easy to adsorb these. In other words, they have an excellent function of adsorbing gas components that do not have functional groups. Furthermore, when alkali metals and alkaline earth metals such as Ca, Na, and K are present on the zeolite surface, the zeolite surface exhibits basicity and is easy to adsorb acidic gases by neutralization reaction.
[0049] (Molecular sieve) Molecular sieves are a type of hydrophilic zeolite that adsorb highly polar molecules into their porous pores, and are particularly adsorbent of water (water vapor) molecules. Molecular sieves are designated as 3A, 4A, 5A, or 13X depending on the type of raw zeolite, where the number indicates the approximate pore diameter (angstroms) and the capital letters indicate the type of zeolite, with A representing LTA zeolite and X representing FAU zeolite. 3A is suitable for adsorbing acetonitrile and ethanol, 5A is suitable for adsorbing aromatic compounds, and 13X is suitable for adsorbing large molecules such as long-chain tertiary amines.
[0050] (Metal-organic framework (MOF)) For metal organic frameworks (MOFs), a salt consisting of a metal ion and an organic ligand is preferably used. The metal-organic framework can have a porous structure with a smaller pore size and a larger specific surface area compared to common activated carbon or zeolite. Specific examples of the metal organic framework include aluminum fumarate, zirconium fumarate, copper trimesate, aluminum trimesate, zirconium trimesate, iron trimesate, aluminum terephthalate, zirconium terephthalate, 2-methylimidazole zinc, magnesium formate, zinc benzene-1,3,5-tribenzoate, zinc 2,6-naphthalene-dicarboxylate, aluminum aminobenzene-1,4-dicarboxylate, magnesium 2,5-dioxidobenzene-1,4-dicarboxylate, and magnesium 4,4-dioxidobiphenyl-3,3-dicarboxylate. One or a combination of two or more selected from this group can be used.
[0051] The pore size of the metal organic framework is preferably 0.3 nm or more and 3.0 nm or less, and more preferably 0.3 nm or more and 2.0 nm or less. For example, the pore size of 2-methylimidazole zinc salt is 1.1 nm and 0.6 nm, that of copper trimesate is 0.90 nm or 0.3 nm and 0.5 nm, that of aluminum terephthalate is 0.8 nm and 0.5 nm, that of aluminum fumarate is 1.1 nm and 0.5 nm, that of aluminum trimesate is 0.7 nm and 0.6 nm, that of zirconium trimesate is 0.46 nm, 1.15 nm, and 1.8 nm, that of magnesium formate is 0.3 nm and 0.4 nm, and that of iron trimesate is 2.5 nm and 2.9 nm.
[0052] The specific surface area of the metal-organic framework can be expressed as a BET specific surface area or a Langmuir specific surface area. In the case of the BET specific surface area, 2 / g or more, 4000m 2 / g or less is preferable. 900m 2 / g or more, 2100m 2 / g or less is more preferable. For Langmuir specific surface area, 500m 2 / g or more, 5000m 2 / g or less is preferable, and 1200m 2 / g or more, 2400m 2 / g or less is more preferable.
[0053] For example, the BET specific surface area of 2-methylimidazole zinc is 1350 m 2 / g, copper trimesate 1500m 2 / g, aluminum terephthalate is 950m 2 / g, aluminum fumarate is 1000m 2 / g, aluminum trimesate is 1100m 2 / g, zirconium trimesate is 2060m 2 / g, magnesium formate is 400m 2 / g, benzene-1,3,5-tribenzoic acid zinc is 3600m 2 There are ones that are / g. For example, the Langmuir specific surface area of 2-methylimidazole zinc is 1800 m 2 / g, copper trimesate 2000m 2 / g, aluminum terephthalate is 1500m 2 / g, aluminum fumarate is 1200m 2 / g, aluminum trimesate 1500m 2 / g, zirconium trimesate 2390m 2 / g, magnesium formate is 500m 2 / g, benzene-1,3,5-tribenzoic acid zinc is 5000m 2 There are ones that are / g.
[0054] The metal organic frameworks described above can absorb gases in amounts corresponding to the molecular size and specific surface area of the pores. For example, 2-methylimidazole zinc salt is excellent in absorbing lower hydrocarbons and carbon dioxide, copper trimesate is excellent in absorbing lower hydrocarbons (especially methane) and carbon dioxide, aluminum terephthalate is excellent in absorbing methane, water vapor, and carbon dioxide, aluminum fumarate and zircon trimesate are excellent in absorbing water vapor, and aluminum trimesate is excellent in absorbing lower hydrocarbons (especially methane) and water vapor.
[0055] In the present invention, among the above metal organic frameworks, it is preferable to use one or a combination of two or more selected from the group consisting of 2-methylimidazole zinc salt, copper trimesate, and aluminum terephthalate.
[0056] (activated carbon) Activated carbon is a porous material that is primarily composed of carbon and also contains oxygen, hydrogen, calcium, etc., and has been chemically or physically processed. Because it is porous, it has a large surface area relative to its volume, and therefore has the ability to adsorb many substances. Since the surface of activated carbon is non-polar, it has a low adsorption power for polar molecules and is more likely to selectively adsorb granular organic matter that is smaller than the pores of activated carbon.
[0057] (Improved dispersion by making gas adsorbents into master batches) The gas adsorbent may be directly mixed with other components of the low outgassing gas adsorbent sealant film and melt-kneaded, but it is preferable to increase the dispersibility of the gas adsorbent in the low outgassing gas adsorbent sealant film by mixing the gas adsorbent with a thermoplastic resin at a high concentration and then melt-kneading (melt blending) to prepare a master batch, and then mixing this with other components of the low outgassing gas adsorbent sealant film in a ratio corresponding to the target content and melt-kneading, a so-called master batch method. By adopting the master batch method, even when a gas adsorbent that is prone to aggregation is used, the gas adsorbent can be efficiently and uniformly dispersed in the low outgassing gas adsorbent sealant film.
[0058] The mass ratio of the gas adsorbent to the thermoplastic resin in the master batch is not particularly limited, but is preferably 3 / 97 or more and 50 / 50 or less, and more preferably 5 / 95 or more and 40 / 60 or less. As a method for kneading the gas adsorbent and the thermoplastic resin, various kneading methods can be applied. The thermoplastic resin used in the masterbatch is low gas emission gas adsorption sealant film The type and content of the resin may be within a range that does not significantly adversely affect the heat sealability, film formability, gas adsorption, or low outgassing of the film, but it is preferable that the resin has high compatibility with other resins, such as the heat sealable resin and low outgassing resin, contained in the low outgassing gas adsorbent sealant film and has the same degree of heat sealability, and may be the same as or different from these. For example, it may be a low outgassing resin.
[0059] Specific examples of the thermoplastic resin used in the masterbatch include, for example, general-purpose polyethylene, polypropylene, methylpentene polymer, polyolefin resins such as acid-modified polyolefin resins, and mixtures of these resins, but are not limited to these resins, and the type of thermoplastic resin can be selected depending on the purpose.
[0060] The MFR (melt flow rate) of the thermoplastic resin used in the master batch is preferably 0.2 g / 10 min or more and 10 g / 10 min or less. If the MFR is in this range, melt mixing with the gas adsorbent is easy, the gas adsorbent is easily dispersed in the low outgassing gas adsorbent sealant film, and the film formability of the low outgassing gas adsorbent sealant film is easily maintained.
[0061] [Antioxidants] The low outgassing gas adsorbent sealant film preferably further contains an antioxidant. The content of the antioxidant in the entire low gas release gas adsorption sealant film is preferably 0.005 mass% or more and 0.5 mass% or less, and more preferably 0.01 mass% or more and 0.4 mass% or less. If the content is less than the above range, the effect of containing the antioxidant may be insufficient, and if the content is more than the above range, the effect of increasing the antioxidant will not change much, and the heat sealability may tend to deteriorate. The antioxidant may be contained in the gas adsorption layer and / or the heat seal layer constituting the low outgassing gas adsorption sealant film, and the antioxidant contained in the gas adsorption layer and the antioxidant contained in the heat seal layer may be the same or different.
[0062] Specific examples of the antioxidant include phenol-based antioxidants, phosphorus-based antioxidants, and mixed phenol- and phosphorus-based antioxidants. It is preferable to contain one or a combination of two or more selected from the group consisting of these antioxidants.
[0063] (Method for producing low outgassing gas adsorption sealant film) For example, a gas adsorption layer resin composition for the gas adsorption layer and a low gas release resin for the heat seal layer are separately prepared and then subjected to an inflation method to obtain a low gas release gas adsorption sealant film having the following layer structure. Layer structure: heat seal layer 1 / gas adsorption layer / heat seal layer 2 Alternatively, the gas adsorption layer resin composition for the gas adsorption layer and the low gas release resin for the heat seal layer may be laminated on a release film by extrusion coating or co-extrusion, and the release film may be removed. In the case of the extrusion coating method, lamination may be performed via an adhesive layer as necessary.
[0064] (Method for measuring gas emission from low gas-emission gas-adsorbing sealant film) The gas release properties of the low outgassing gas adsorbing sealant film of the present invention can be measured, for example, by cutting the low outgassing gas adsorbing sealant film to 50 mm x 10 mm, placing the obtained two rectangular films in a test tube and heating them at 90°C for 60 minutes, collecting the air in the test tube, and measuring the concentrations of organic gas components with each carbon number in the collected air by gas chromatography, and calculating the amount of organic gas components released by the low outgassing gas adsorbing sealant film when heated. Among organic gas components, the amount of C16 gas components (organic gas components with carbon number 16) is particularly low. It is highly correlated with thermal conductivity in vacuum insulation panels made using low outgassing, gas adsorbing packaging materials having a sealant layer formed from an outgassing, gas adsorbing sealant film.
[0065] The amount of C16 gas component released when the low outgassing gas adsorbent sealant film is heated, as determined by the above method, per unit volume of the low outgassing gas adsorbent sealant film is 10 μg / cm 3 More than 1000μg / cm 3 It is preferable that:
[0066] (Method for measuring gas adsorption of low gas-releasing gas adsorption sealant film) The gas adsorption of the low outgassing gas adsorbent sealant film of the present invention can be measured by cutting the low outgassing gas adsorbent sealant film to, for example, a size of 10 cm x 10 cm, placing it in a gas sampling bag, filling it with a gas to be adsorbed of known concentration, and allowing it to stand for two days, after which the change in gas concentration can be measured using a detector tube.
[0067] <Low gas release gas adsorption laminate> The gas adsorbing laminate with low outgassing property of the present invention is a laminate having a gas adsorbing sealant layer with low outgassing property, has heat sealability, low outgassing property, and is capable of adsorbing gas. The low outgassing gas adsorbing sealant layer is a layer formed from the low outgassing gas adsorbing sealant film of the present invention, and contains a low outgassing resin and a gas adsorbent, and the low outgassing resin is preferably a low outgassing resin having heat sealability. The gas adsorbent laminate with low gas release properties of the present invention preferably further comprises a substrate layer, and the substrate layer is more preferably a gas barrier substrate layer. Due to the above characteristics, the low outgassing gas adsorbent laminate is suitable for use as a laminate for vacuum packaging, similar to the low outgassing gas adsorbent sealant film of the present invention.
[0068] In order to maintain the reduced pressure state of the package, it is necessary to suppress the increase in gas molecules inside the package. To achieve this, it is necessary to suppress the amount of gas released from the low outgassing gas adsorbing laminate, particularly the low outgassing gas adsorbing sealant layer itself, the amount of gas that penetrates through the thickness of the low outgassing gas adsorbing laminate and enters the inside of the package, and the amount of gas that penetrates through the interface of the joints formed by heat sealing, etc. of the low outgassing gas adsorbing laminate.
[0069] Of the gas released from the low outgassing gas adsorbing laminate itself inside the package, a large amount is released from the low outgassing gas adsorbing sealant layer of the low outgassing gas adsorbing laminate, and the low outgassing gas adsorbing heat seal layer is present at the interface of the joint portion of the low outgassing gas adsorbing laminate by heat sealing, etc., and the low outgassing gas adsorbing sealant layer is in contact with the internal space of the package. Therefore, the low outgassing gas-adsorbing sealant layer of the low outgassing gas-adsorbing laminate of the present invention generates a small amount of gas itself, has excellent heat sealing properties, and adsorbs gas from the space with which the low outgassing gas-adsorbing sealant layer is in contact, thereby adsorbing gas that penetrates into the inside of the package through the interface of the joint and gas that has permeated the barrier substrate layer, thereby preventing the gas from reaching the inside of the package, and also adsorbs gas present inside the package, thereby preventing an increase in air pressure inside the package and maintaining a reduced pressure state.
[0070] The gas releasing property and gas adsorbing property of the low gas releasing and gas adsorbing laminate of the present invention can be measured by the same method as that for the low gas releasing and gas adsorbing sealant film.
[0071] <Gas barrier substrate layer> The gas barrier substrate layer in the present invention refers to a substrate layer having gas barrier properties, and is composed of one layer such as a gas barrier resin film having gas barrier properties and substrate properties. Alternatively, the gas barrier layer may have a multi-layer structure including a gas barrier layer and a substrate layer. Furthermore, in order to improve adhesion, an adhesive layer may be provided between each layer constituting the gas barrier substrate layer or between each layer and other layers, and a desired surface treatment layer may be provided in advance on the surface of each layer as necessary.
[0072] For example, a corona-treated layer, an ozone-treated layer, a plasma-treated layer, an oxidation-treated layer, or the like can be formed by optionally carrying out pretreatment such as corona discharge treatment, ozone treatment, low-temperature plasma treatment using oxygen gas or nitrogen gas, or the like, glow discharge treatment, or oxidation treatment using chemicals, or the like.
[0073] Alternatively, various coating layers such as a primer coating layer, an undercoating layer, an anchor coating layer, an adhesive layer, and a vapor-deposited anchor coating layer may be optionally formed on the surface of each layer to form a surface treatment layer. For the various coating agent layers, for example, a resin composition containing a polyester-based resin, a polyamide-based resin, a polyurethane-based resin, an epoxy-based resin, a phenol-based resin, a (meth)acrylic resin, a polyvinyl acetate-based resin, a polyolefin-based resin such as polyethylene or polypropylene, or a copolymer or modified resin thereof, a cellulose-based resin, or the like as the main component of the vehicle can be used. The thickness of the gas barrier substrate layer is preferably 5 μm to 100 μm, more preferably 7 μm to 75 μm. If the thickness is less than the above range, the rigidity and / or gas barrier properties may be insufficient, and if the thickness exceeds the above range, the rigidity may be too high, resulting in reduced workability.
[0074] [Base material layer] The substrate layer may be a resin film, a paper material, or the like, and may be composed of a single layer or a multilayer structure including two or more layers having the same or different compositions.
[0075] The thickness of the substrate layer varies depending on the material, but in the case of a resin film, it is preferably 5 μm or more and 60 μm or less, more preferably 7 μm or more and 45 μm or less. The resin film used for the base layer may be a film of a thermoplastic resin, and is preferably a thermoplastic resin that has excellent chemical and physical strength, can withstand the conditions for forming a vapor-deposited film of a metal or metal oxide, and can well retain the properties of the vapor-deposited film without impairing the properties.
[0076] Examples of such resins include polyolefin resins such as polyethylene resins and polypropylene resins, cyclic polyolefin resins, polystyrene resins, acrylonitrile-styrene copolymers (AS resins), acrylonitrile-butadiene-styrene copolymers (ABS resins), poly(meth)acrylic resins, polycarbonate resins, polyester resins such as polyethylene terephthalate and polyethylene naphthalate, polyamide resins such as various nylons, polyurethane resins, acetal resins, and cellulose resins. In the present invention, the resin is preferably a polyester resin, a polyamide resin, or a polyolefin resin, and in particular, polyethylene terephthalate (PET), nylon, or polypropylene (PP).
[0077] In the present invention, the thermoplastic resin used in the substrate layer can be formed into a film by various film-forming methods. For example, a method of forming a film using one type of resin by a film forming method such as an extrusion method, a cast molding method, a T-die method, a cutting method, or an inflation method, a method of forming a multi-layer film by co-extrusion using two or more types of resins, a method of mixing two or more types of resins before film formation, and forming a film by the above-mentioned film formation method. Furthermore, a film can be uniaxially or biaxially stretched using a tenter method, a tubular method, or the like.
[0078] Alternatively, one or more resins may be coated on another resin film by applying and drying, or a molten resin may be laminated by a T-die method or the like. In the present invention, the resin film is preferably a biaxially oriented PET film, a biaxially oriented nylon film, or a biaxially oriented PP film or sheet.
[0079] In addition, when forming the resin film, various plastic compounding agents and additives can be added to the resin film for the purpose of improving or modifying, for example, the processability, heat resistance, weather resistance, mechanical properties, dimensional stability, oxidation resistance, slipperiness, release properties, flame retardancy, mold resistance, electrical properties, strength, etc. of the film. The amount of these additives can range from a very small amount to several tens of percent and can be added at any amount depending on the purpose. In the above, examples of common additives that can be used include lubricants, crosslinking agents, antioxidants, ultraviolet absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, modifying resins, and the like.
[0080] [Gas barrier layer] The gas barrier layer is a layer that, in a packaging body made using the low outgassing gas adsorption laminate of the present invention, prevents atmospheric gas from passing through the low outgassing gas adsorption laminate from the outside to the inside of the packaging body. The gas barrier layer may be made of one or a combination of two or more selected from the group consisting of a gas barrier resin film, a metal foil, a resin film with a metal or metal oxide vapor-deposited layer, and a gas barrier resin coating film.
[0081] As the gas barrier resin film, for example, a resin film made of a resin such as PET, polybutylene terephthalate, polyethylene naphthalate, polyamide, polyimide, polyvinyl alcohol, or an ethylene-vinyl alcohol copolymer is preferable.
[0082] The metal foil is preferably an aluminum foil having a thickness of 3 μm or more and 15 μm or less.
[0083] The resin film with a metal or metal oxide vapor deposition layer is preferably one in which an aluminum vapor deposition film, a silica vapor deposition film, or an aluminum oxide vapor deposition film is formed on at least one surface of the above-mentioned base resin film. Commercially available resin films with an aluminum oxide vapor deposition film include, for example, alumina vapor deposition IB-PET-PIR (thickness 12 μm) and silica vapor deposition IB-ON-UB (thickness 15 μm) manufactured by Dai Nippon Printing Co., Ltd., which are PET films with alumina vapor-deposited on one side by the PVD method.
[0084] As the gas barrier resin coating film, a coating film containing a sol-gel hydrolysis polycondensate formed from a metal alkoxide and a water-soluble polymer is preferred.
[0085] The metal foil for the gas barrier layer, or the resin film with the metal or metal oxide vapor-deposited layer can be bonded to other layers using a dry lamination adhesive. Alternatively, by using a resin film for the base layer as the resin film of the resin film with a metal or metal oxide vapor-deposited layer, lamination onto the base layer can be omitted.
[0086] <Adhesive layer> The gas adsorbent laminate with low outgassing properties of the present invention can be laminated by providing adhesive layers between the constituent layers and between layers within each layer. In addition, before forming the adhesive layer, an anchor is preliminarily applied to the surface of the layer to be adhered in order to improve adhesion. A coating layer may be formed.
[0087] The adhesive (adhesive composition) forming the adhesive layer may be of a thermosetting type, an ultraviolet-curing type, an electron beam-curing type, or the like, and may be in any form, such as an aqueous type, a solution type, an emulsion type, a dispersion type, or the like. In addition, the adhesive may be in any form, such as a film / sheet type, a powder type, a solid type, or the like, and the adhesive mechanism may be in any form, such as a chemical reaction type, a solvent volatilization type, a thermal melting type, a thermal pressure type, or the like.
[0088] Examples of such adhesives include polyvinyl acetate adhesives such as polyvinyl acetate and vinyl acetate-ethylene copolymers, polyacrylic acid adhesives made of copolymers of polyacrylic acid and polystyrene, polyester, polyvinyl acetate, etc., cyanoacrylate adhesives, ethylene copolymer adhesives made of copolymers of ethylene and monomers such as vinyl acetate, ethyl acrylate, acrylic acid, methacrylic acid, etc., cellulose adhesives, polyurethane adhesives, polyester adhesives, polyamide adhesives, polyimide adhesives, polyolefin adhesives, amino resin adhesives made of urea resin or melamine resin, etc., phenol resin adhesives, epoxy adhesives, reactive (meth)acrylic adhesives, elastomer adhesives made of chloroprene rubber, nitrile rubber, styrene-butadiene rubber, etc., silicone adhesives, inorganic adhesives made of alkali metal silicates, low-melting point glass, etc. When a laminate is formed by coextrusion and film formation using an inflation method, among the above, polyolefin-based adhesives are preferred.
[0089] In one embodiment of the present invention, the adhesive layer may be a layer made of any of an adhesive for EC (extrusion coating), an adhesive for dry lamination, an adhesive for non-solvent lamination, and the like. When an EC adhesive is used, although there are no particular limitations, for example, the adhesive is first heated and melted, expanded and stretched in the required width direction using a T-die or the like, extruded into a curtain shape, allowed to flow down onto the layer to be bonded, and then sandwiched between a rubber roll and a cooled metal roll, thereby simultaneously forming an adhesive layer and bonding and laminating to the layer to be bonded.
[0090] In another embodiment, the adhesive layer may be formed by sand lamination. In this case, any resin that can be applied by heating and melting in an extruder can be used for the adhesive layer. Specifically, the resins listed above as thermoplastic resins having heat sealability can be preferably used.
[0091] When using a dry lamination adhesive, the adhesive dispersed or dissolved in a solvent is applied onto one film and dried, and the other film is then laminated on top of it. The adhesive is then cured by aging at 30 to 120°C for several hours to several days to bond and laminate the films.
[0092] When using a non-solvent laminating adhesive, the adhesive itself is applied to the layer to be adhered without being dispersed or dissolved in a solvent, and then dried. The film that forms the other layer is then laminated on top of the adhesive, and the adhesive is hardened by aging at 30 to 120°C for several hours to several days before laminating.
[0093] The adhesive for dry lamination or the adhesive for non-solvent lamination can be used by coating, for example, by roll coating, gravure roll coating, kiss coating, etc., and the coating amount is 0.1 to 10 g / m 2 By setting the coating amount within the above range, good adhesion can be obtained.
[0094] (Anchor coat layer) The anchor coat layer can be formed from any anchor coat agent. Examples of anchor coating agents that can be used include organic titanium-based, isocyanate (urethane-based), polyethyleneimine-based, acid-modified polyethylene-based, polybutadiene-based, polyacrylic-based, polyester-based, epoxy-based, polyvinyl acetate-based, cellulose-based, and other anchor coating agents.
[0095] [Method for producing low gas release gas adsorption laminate] The preparation method described below is an example and is not intended to limit the present invention. The formation of each layer constituting the low gas release gas adsorption laminate can be carried out by any method, such as wet lamination, dry lamination, solventless dry lamination, extrusion lamination, T-die coextrusion molding, coextrusion lamination, inflation molding, and the like. The obtained low gas release gas adsorption laminate can be subjected to secondary processing for the purpose of imparting surface functions such as chemical functions, electrical functions, magnetic functions, mechanical functions, friction / wear / lubrication functions, optical functions, thermal functions, and biocompatibility.
[0096] Examples of secondary processing include embossing, painting, adhesives, printing, metallizing (plating, etc.), machining, surface treatment (antistatic treatment, corona discharge treatment, plasma treatment, photochromic treatment, physical vapor deposition, chemical vapor deposition, coating, etc.), and the like.
[0097] As an example, the following describes the production of a low outgassing gas adsorption laminate (reduced pressure retention packaging material) having a layer structure of gas barrier substrate layer [substrate layer 1 / adhesive layer / substrate layer 2 / adhesive layer / gas barrier layer] / adhesive layer / low outgassing gas adsorption sealant layer [heat seal layer 1 / gas adsorption layer / heat seal layer 2].
[0098] (Preparation of low outgassing gas adsorption sealant film) A gas adsorption layer resin composition for the gas adsorption layer and a low gas releasing resin for the heat seal layer are separately prepared and then subjected to an inflation method to obtain a low gas releasing gas adsorption sealant film having the layer structure described below. Layer structure: heat seal layer 1 / gas adsorption layer / heat seal layer 2
[0099] (Preparation of low gas release gas adsorption laminate) Next, the low outgassing gas adsorption sealant film obtained above for the low outgassing gas adsorption sealant layer, the base film 1 for the base layer 1, the base film 2 for the base layer 2, and an aluminum foil for the gas barrier layer were dry laminated in this order via a DL adhesive for the adhesive layer (coating amount: 3.5 g / m 2 , drying temperature: 70° C., to obtain a gas adsorbing laminate with low gas release properties having the above layer structure.
[0100] <Low gas emission and gas adsorption packaging material> The low outgassing gas adsorbing packaging material of the present invention is a packaging material made from the low outgassing gas adsorbing laminate of the present invention, and may be the same as the low outgassing gas adsorbing laminate, and may further include various functional layers, printed layers, etc., as necessary. Due to the above characteristics, the gas adsorbing packaging material with low outgassing property is suitable as a packaging material for vacuum packaging, like the gas adsorbing laminate with low outgassing property of the present invention. The low gas-releasing, gas-adsorbing packaging material of the present invention can also be subjected to lamination (dry lamination or extrusion lamination), bag making, and other post-treatments. Specific examples of the low gas emission, gas adsorption packaging material of the present invention include low gas emission, gas adsorption packaging materials for various vacuum packaging. Examples of vacuum packaging include fresh foods (cheese, salami, sausages, etc. that are not sterilized after vacuum packing) and boiled and retort foods (vacuum packed and then sterilized). In addition, in the industrial materials field, examples of applications include outer packaging materials for heat insulating panels, and anti-rust packaging materials for metal parts or metal equipment.
[0101] <Low gas emission gas adsorption packaging> The low outgassing, gas-adsorbing packaging body of the present invention is a packaging body produced using the low outgassing, gas-adsorbing packaging material of the present invention, and specific examples include food packaging bodies, insulation panels, and rust-proof packaging bodies. EXAMPLES
[0102] Details of the raw materials used in the examples are as follows. [Low gas emission resin] Low gas emission resin 1: Urutozex 3520L, manufactured by Prime Polymer Co., Ltd. C6-LLDPE, density 0.931g / cm 3 , MFR 2.1g / 10min. TOC concentration in the extracted water was 0.26ppm, and the elutable TOC concentration in the resin film was 42.3ppm. Low gas emission resin 2: Prime Polymer Co., Ltd., Neozex 3510F. C4-LLDPE, density 0.933g / cm 3 , MFR 1.6g / 10min. TOC concentration in the extracted water was 0.32ppm, and the elutable TOC concentration in the resin film was 52.0ppm. Low gas emission resin 3: Urutozex 2021L, manufactured by Prime Polymer Co., Ltd. C6-LLDPE, density 0.919g / cm 3 , MFR 2.0g / 10min. TOC concentration in the extracted water was 0.56ppm, and the elutable TOC concentration in the resin film was 92.3ppm. Low gas emission resin 4: Novatec LC522, manufactured by Japan Polyethylene Co., Ltd. LDPE. Density 0.923g / cm 3 , MFR4g / 10min. TOC concentration in the extracted water was 0.32ppm, and the elutable TOC concentration in the resin film was 52.5ppm.
[0103] [General-purpose polyethylene] General-purpose polyethylene 1: Evolu SP4020 manufactured by Prime Polymer Co., Ltd. C6-LLDPE, density 0.937g / cm 3 , MFR 1.7g / 10min. TOC concentration in the extracted water was 2.85ppm, and the elutable TOC concentration in the resin film was 461ppm. General-purpose polyethylene 2: Prime Polymer Co., Ltd., Evolu SP1520. C6-LLDPE, density 0.913g / cm 3 , MFR 2.0g / 10min. TOC concentration in the extracted water was 3.05ppm, and the elutable TOC concentration in the resin film was 506ppm.
[0104] [Gas adsorbent] Hydrophobic zeolite 1: Mizusawa Chemical Industry Co., Ltd. hydrophobic zeolite, Mizuka Sieves EX-122. SiO2 / AL2O3 molar ratio = 32 / 1, average particle size = 2.5 to 5.5 μm. Hydrophobic zeolite 2: Silton MT400, a hydrophobic zeolite manufactured by Mizusawa Chemical Industry Co., Ltd. SiO2 / AL2O3 molar ratio = 400 / 1, average particle size = 5 to 7 μm. Hydrophobic zeolite 3: Silton MT-2000, a hydrophobic zeolite manufactured by Mizusawa Chemical Industry Co., Ltd. SiO2 / AL2O3 molar ratio = 2000 / 1, average particle size = 0.8 μm.
[0105] [Antioxidants] Antioxidant 1: EAG-5, manufactured by Prime Polymer Co., Ltd. Contains a total of 5% by mass of phenol-based antioxidant and phosphorus-based antioxidant. MFR 4.5g / 10min.
[0106] [Film for base layer] PET film 1: Toyobo Co., Ltd., Espet T4102, thickness 12 μm. [Metal foil for barrier layer] Aluminum foil 1: Manufactured by Toyo Aluminum Co., Ltd. Thickness: 6 μm. [glue] DL Adhesive 1: Adlock RU77T / H7, manufactured by Rock Paint Co., Ltd.
[0107] [Preparation of master batch] The masterbatch used in the gas adsorption layer was prepared as follows.
[0108] (Preparation of Masterbatch 1) Low gas releasing resin 4 and hydrophobic zeolite 1 were melt blended in the following ratio to obtain master batch 1 (MB1). Low gas emission resin 4 90 parts by weight Hydrophobic zeolite 1 10 parts by weight
[0109] [Adjustment of Masterbatches 2 to 7] According to the formulation in Table 1, the raw materials were melt-blended in the same manner as for Masterbatch 1 to obtain Masterbatches 2 to 7 (MB2 to 7).
[0110] [Table 1]
[0111] [Preparation of Gas Adsorption Layer Resin Composition] The gas adsorbing layer resin composition used in the gas adsorbing layer was prepared as follows.
[0112] (Preparation of Gas Adsorption Layer Resin Composition 1) The MB1 and the low gas releasing resin 1 were dry blended in the following ratio to obtain a gas adsorbing layer resin composition 1. MB1 16.7 parts by mass Low gas emission resin 1 83.3 parts by mass
[0113] (Preparation of Gas Adsorption Layer Resin Compositions 2 to 13) According to the formulation shown in Table 2, the raw materials were dry-blended in the same manner as in gas-adsorbing layer resin composition 1 to obtain gas-adsorbing layer resin compositions 2 to 13.
[0114] [Table 2]
[0115] [Table 3]
[0116] [Preparation of Heat Seal Layer Resin Composition] The raw materials were dry-blended according to the composition shown in Table 3 to obtain resin compositions 1 and 2 for the heat seal layer.
[0117] [Table 4]
[0118] <Example 1> The gas adsorption layer resin composition 1 obtained above and the low gas release resin 1 were used to produce an inflation gas. By the coating method, a low gas releasing gas adsorbing sealant film 1 having the following layer structure was obtained. Heat seal layer 1 / gas adsorption layer / heat seal layer 2=low gas release resin 1 (10 μm thick) / gas adsorption layer resin composition 1 (30 μm thick) / low gas release resin 1 (10 μm thick) The obtained low gas release gas adsorption sealant film 1 was used for various evaluations. Furthermore, the low gas release gas adsorption sealant film 1 obtained above, the PET film 1, and the aluminum foil 1 were dry laminated with the DL adhesive 1 (coating amount: 3.5 g / m 2 The laminate was laminated together at 100° C. (drying temperature: 70° C.) to obtain a gas adsorbent laminate 1 with low gas release properties having the following layer structure, and the heat sealability was evaluated. The layer structure and evaluation results are shown in Table 5. Structure of laminate 1: Gas barrier substrate layer (PET film 1 / DL adhesive 1 / aluminum foil 1 / DL adhesive 1 / low gas release gas adsorption sealant film 1)
[0119] <Examples 2 to 17 and Comparative Examples 1 to 4> Using the raw materials shown in Tables 5 to 8, and following the same procedure as in Example 1, low outgassing gas adsorbent sealant films and low outgassing gas adsorbent laminates were obtained and similarly evaluated.
[0120] <Evaluation method> [Film forming property] The appearance of the low outgassing gas adsorbent sealant film was observed and evaluated sensorily according to the following criteria: ○: Film formation is possible without wrinkles or bumps. ×: Numerous wrinkles and bumps were generated, making film formation difficult.
[0121] [Gas release amount] The low outgassing gas adsorption sealant film was cut to 50 mm x 10 mm, and two pieces of film were placed in a test tube and heated at 90°C for 60 minutes. The air in the test tube was sampled and the concentration of the carbon number 16 organic gas component in the sampled air was measured by gas chromatography, and the amount of the carbon number 16 organic gas component released per unit volume by the low outgassing gas adsorption sealant film was calculated.
[0122] [Gas adsorption] The low gas emission gas adsorption sealant film was cut to 10 x 10 cm and placed in a gas sampling bag (GL Sciences, SMART BAG) together with 600 cc of acetaldehyde gas adjusted to 100 ppm. After leaving it for 2 days, the gas concentration was measured using a detector tube (Gastec, Acetaldehyde No. 92M). In addition, instead of acetaldehyde gas, acetic acid gas adjusted to 30 ppm and ethyl acetate gas adjusted to 400 ppm were used to carry out the evaluation in the same manner as for acetaldehyde gas. For the gas concentration measurement, the detector tubes used were "Gastec Corporation, Acetic Acid No. 81" for acetic acid gas and "Gastec Corporation, Ethyl Acetate No. 141L" for ethyl acetate gas.
[0123] [Heat sealability] The low gas-releasing gas-adsorbing laminate was cut into 10 cm x 10 cm pieces, the heat-sealed surfaces were overlapped, and a 1 cm x 10 cm area was heat-sealed under the following conditions using a heat seal tester (TP-701-A manufactured by Tester Sangyo Co., Ltd.) to produce a peel strength test piece in which the ends were not heat-sealed or bonded, and the pieces were split into two. This test piece was cut into a strip of 15 mm width, and each bifurcated end was attached to a tensile tester to measure the peel strength (N / 15 mm) under the conditions below, and the pass / fail judgment was made according to the pass / fail judgment criteria below. Heat sealing conditions Temperature: 160℃ Pressure: 1kgf / cm 2 Time: 1 second Test conditions Test speed: 300mm / min Load range: 50N Pass / Fail Criteria ○: 30N / 15mm or more, passed. ×: Less than 30N / 15mm, failing.
[0124] [TOC concentration] Water was filled into a pouch made of a resin film, which was then sealed and stored at 35° C. for 2 weeks. The TOC concentration of the water was then measured to determine the increase in the TOC concentration of the water. Pouch size: inner dimensions 15cm x 44cm x 50μm thick. Filling water: Distilled water for high performance liquid chromatography manufactured by Junsei Chemical Co., Ltd. 65°C 1000g. TOC concentration measuring device: TOC-L total organic carbon meter manufactured by Shimadzu Corporation. Next, the concentration of elutable TOC contained in the resin film was calculated from the increased concentration of TOC in the filling water obtained above using the following formula. C = X × W1 / W2 =X×W1 / (6.6×S) C: Concentration of elutable TOC contained in the resin film [ppm] X: Increase in TOC concentration in filling water [ppm] W1: Filled water weight = 1000[g] W2: Pouch weight = 15 x 44 x 50 x 10 -4 ×2×S=6.6×S[g] S: Density of resin film [g / cm 3 ]
[0125] [Table 5]
[0126] [Table 6]
[0127] [Table 7]
[0128] [Table 8]
[0129] <Summary of results> The low gas-releasing, gas-adsorbing sealant films of the present invention in all the Examples exhibited good film-forming properties, low gas-releasing properties, and excellent adsorption properties for various gas components. However, Comparative Examples 1 to 3, which contain an insufficient amount of low gas release resin, tend to release a large amount of gas, and Comparative Example 1, which does not contain a gas adsorbent, tends to have a low adsorption effect on various gas components. did. Moreover, in Comparative Example 4, in which the gas adsorbent content in the gas adsorption layer was too high, the gas adsorption effect was good, but the film formability was poor. [Explanation of symbols]
[0130] 1. Low gas emission and gas adsorption sealant film 2. Low gas emission gas adsorption laminate 3. Low gas emission and gas absorbing packaging materials 4a Gas adsorption layer 4b Gas adsorbent 4c Heat seal layer 7 Gas barrier substrate layer 8. Low outgassing gas adsorption sealant layer 9 Adhesive layer 10. Low gas emission, gas adsorption packaging 11 Primary container of contents or structural support 12 Heat seal joint
Claims
1. A low gas-releasing gas-adsorbing sealant film that adsorbs gas generated from the sealant film itself and gas from a space that the sealant film contacts, The low gas release gas adsorption sealant film has a heat seal layer, a gas adsorption layer, and a heat seal layer laminated in this order (excluding the case where the heat seal layer contains a friction resistance reducing agent consisting of a slip agent and an antiblocking agent), The gas adsorption layer is a layer containing a low gas release resin and a gas adsorbent, the heat seal layer contains a low gas releasing resin and has heat sealability; the low gas-releasing resin contained in the gas adsorption layer is the same as the low gas-releasing resin contained in the heat seal layer, the gas is one or a combination of two or more selected from the group consisting of hydrocarbons, aldehydes, ketones, carboxylic acids, esters, alcohols, and carbon dioxide; The low gas emission resin has a density of 0.915 g / cm 3 Above, 0.935g / cm 3 is as follows: The content of the low gas release resin in the entire low gas release gas adsorption sealant film is 70% by mass or more and 99.9% by mass or less, The low gas emission resin is a polyethylene resin, The gas adsorbent comprises one or a combination of two or more selected from the group consisting of hydrophobic zeolite, molecular sieve, metal-organic framework (MOF), and activated carbon; the content of the gas adsorbent in the layer containing the gas adsorbent is 0.1% by mass or more and 30% by mass or less, The low outgassing gas adsorption sealant film has a carbon number of 16 organic gas component released when heated in air at 90° C. for 60 minutes, and the amount of the low outgassing gas adsorption sealant film per unit volume of the low outgassing gas adsorption sealant film is 10 μg / cm 3 Above, 1000μg / cm 3 Below is the The low outgassing gas adsorbing sealant film.
2. The low gas emission gas adsorption sealant film according to claim 1, characterized in that the concentration of elutable total organic carbon (TOC) contained in the film made of the low gas emission resin is 1.5 ppm or more and 250 ppm or less.
3. The low gas release gas adsorption sealant film according to claim 1 or 2, characterized in that the low gas release resin is one or a combination of two or more selected from the group consisting of medium density polyethylene, low density polyethylene and linear low density polyethylene.
4. The gas-adsorbing sealant film with low outgassing property according to any one of claims 1 to 3, further comprising an antioxidant.
5. 5. The gas adsorbing sealant film with low outgassing property according to claim 4, characterized in that the content of the antioxidant is 0.005 mass % or more and 0.5 mass % or less in the total gas adsorbing sealant film with low outgassing property.
6. the antioxidant is contained in the gas adsorption layer and / or the heat seal layer, The antioxidant contained in the gas adsorption layer and the antioxidant contained in the heat seal layer are the same or different.
6. The low outgassing gas adsorbent sealant film according to claim 4 or 5.
7. A gas adsorbing laminate with low outgassing properties, produced using the gas adsorbing sealant film with low outgassing properties according to any one of claims 1 to 6.
8. A gas adsorbing packaging material with low outgassing properties, produced using the gas adsorbing laminate according to claim 7.
9. A gas adsorbing package with low gas emission, produced using the gas adsorbing packaging material according to claim 8.
Citation Information
Patent Citations
Deoxidizing resin composition
JP1999323032A
Vacuum heat insulating material
JP2008087176A
Package for vegetables and fruits
JP2017100740A
Exterior material for vacuum heat insulation material
JP2018189220A
Sealant film for liquid content packaging, packaging material for liquid content, and package for liquid content
JP2019064630A